Computational thinking process of high school students in solving sequences and series problems - Nurul Izatul Azizah; Yenita Roza; Maimunah Maimunah (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2022)
Kemampuan berpikir komputasi merupakan keterampilan berpikir yang dibutuhkan pada abad 21. Penelitian ini bertujuan untuk mendeskripsikan proses berpikir komputasi siswa SMA/MA dalam menyelesaikan masalah barisan dan deret. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan tes dan wawancara. Subjek dalam penelitian ini adalah siswa kelas XI IPA MA Muhammadiyah Kota Pekanbaru sebanyak 15 orang. Analisis terhadap kemampuan berpikir komputasi siswa dilihat melalui indikator. Hasil analisis menunjukkan bahwa siswa yang berkemampuan tinggi berada dalam kategori sangat baik pada indikator dekomposisi (87,5%) dan abstraksi (97,5%), kategori baik pada indikator berpikir algoritma (65%) dan kategori cukup pada indikator pengenalan pola (50%). Siswa berkemampuan sedang dalam kategori baik pada indikator abstraksi (62%), kategori cukup pada indikator dekomposisi (51,5%), kategori rendah pada indikator pengenalan pola (33,5%) dan berpikir algoritma (39%). Siswa berkemampuan rendah berada dalam kategori rendah untuk tiga indikator yaitu dekomposisi (38,3%), abstraksi (33,3%), berpikir algoritma (21,7%), dan kategori sangat rendah pada pengenalan pola (11,67%). The ability of computational thinking is logical thinking that is needed in the 21st century. This research aims to describe the process of computational thinking in the Senior High School students in completing the problem of arithmetic sequence and series. This research is descriptive research using a qualitative approach. The data collection technique uses tests and interviews. Furthermore, the subject of the research is 15 students of class XI IPA at MA Muhammadiyah Pekanbaru. The students’ computational thinking could be seen through decomposition indicators, pattern recognition, abstraction, and algorithmic thinking. The results of the analysis indicate that students with high abilities are in a very good category on the decomposition indicators (87.5%) and abstraction (97.5%), good categories on the algorithmic thinking indicator (65%), and, the moderate category on the indicators. pattern recognition (50%). For students with moderate abilities, they are in a good category on the abstraction indicator (62%), sufficient category on the decomposition indicator (51.5%), the low category on the pattern recognition indicator (33.5%), and algorithmic thinking (39%). Meanwhile, low-ability students are in the low category for three indicators, namely decomposition (38.3%), abstraction (33.3%), algorithmic thinking (21.7%), and very low category on pattern recognition indicators (11.67%).